Assessment of 83 pharmaceuticals in WWTP influent and effluent samples by UHPLC-MS/MS: Hourly variation - Paíga, Paula (2020)
The removal efficiency of pharmaceuticals in wastewater treatment plants (WWTPs) is variable and some of these compounds pass these plants almost intact and others presenting a removal efficiency close to 100%. Their incomplete removal results in a continuous discharge of pharmaceuticals into the environment. To assess the profile of contamination of influents and effluents over a day, a set of 83 pharmaceuticals were evaluated hourly in a WWTP in Leiria, Portugal. The composite samples of the influent and effluent were also collected. Concentrations varied from <MDL for ketoprofen, clarithromycin, ofloxacin, and diltiazem to 63.97 μg/L for caffeine in the WWTP influent composite sample and <MDL for clarithromycin, bupropion, and diltiazem to 2.01 μg/L for O-desmethylvenlafaxine for effluent composite sample. Concentrations in the range of μg/L were found for hydroxyibuprofen, salicylic acid, d,l-norephedrine, and caffeine in the WWTP influent, and diclofenac, carbamazepine, O-desmethylvenlafaxine in the WWTP effluents. For the samples collected hourly, thirty-eight and twenty-nine pharmaceuticals were detected in at least one WWTP sample. In the WWTP influent the total concentration of detected pharmaceuticals was higher between 15 and 22 h and lower in the period from 23 to 10 h in the morning. In the WWTP effluent, a slight variation was noticed throughout the sampling hours. Carbamazepine, fluoxetine, sertraline, atorvastatin, caffeine, simvastatin, and trazodone were the pharmaceuticals with risk quotient (RQ) >1 in WWTP influents, and carbamazepine, fluoxetine, sertraline the pharmaceuticals with an RQ > 1 in WWTP effluents.